Complications Following COVID-19 Infection or Vaccination in Libyan International Medical University Students and Their Families - Aisha Alfituri; Alasbily, Hamza; Fatima Alanieze; Sarah Bujazia; Talal Aboutrabah (AlQalam Journal of Medical and Applied Sciences, 2024)
Coronavirus disease 2019 (COVID-19) caused by a novel strain of coronavirus belonging to the genus Beta coronavirus named Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) emerged as a major pandemic worldwide. This contagious virus had spread in many different forms, and patients have demonstrated a wide range of symptoms, ranging from moderate to severe illness. This study aims to highlight the important associations between SARS-CoV-2 infection, vaccination, and possible complications at the Libyan International Medical University, Benghazi. This cross-sectional survey was conducted among students and their families at Libyan International Medical University in Benghazi, Libya. Among the 100 participants, 72% were between the ages of 18 and 39. Up to (59%) of participants were men. As for the infection with COVID-19, 77% of participants were infected. Most of the participants had no chronic diseases (69%); however, the most common chronic disease was diabetes mellitus (13%). 82% of participants were vaccinated; the most common types of vaccines administered were Sinopharm and Sputnik V (24%). Following vaccination, 71% of participants had no COVID-19 infection, while 29% did get the infection. Regarding this study, after COVID-19 infection, 66% of participants had no complications; however, 17% had pulmonary complications, which was the most common complication among the participants. As for the complications following the vaccination, 81% of participants had none, while there were pulmonary and neurological complications in 7–6%. The results of the study showed that the most frequent complications noticed among the participants following the COVID-19 infection and vaccination were pulmonary and neurological complications. ظهر مرض فيروس كورونا 2019 (كوفيد-19) الناجم عن سلالة جديدة من فيروس كورونا تنتمي إلى جنس فيروس كورونا بيتا المسمى فيروس كورونا المتلازمة التنفسية الحادة الوخيمة 2 (سارس-كوف-2) كجائحة كبرى في جميع أنحاء العالم. وقد انتشر هذا الفيروس المعدي بأشكال مختلفة، وأظهر المرضى مجموعة واسعة من الأعراض، تتراوح بين المرض المعتدل والشديد. تهدف هذه الدراسة إلى تسليط الضوء على الارتباطات المهمة بين الإصابة بفيروس سارس-كوف-2 والتطعيم والمضاعفات المحتملة في الجامعة الليبية الدولية للعلوم الطبية في بنغازي. أُجري هذا المسح المقطعي بين الطلاب وعائلاتهم في الجامعة الليبية الدولية للعلوم الطبية في بنغازي، ليبيا. من بين 100 مشارك، كان 72% منهم تتراوح أعمارهم بين 18 و39 عامًا. وكان ما يصل إلى (59%) من المشاركين من الرجال. أما بالنسبة للإصابة بفيروس كورونا المستجد (كوفيد-19)، فقد أصيب 77% من المشاركين. لم يكن معظم المشاركين مصابين بأمراض مزمنة (69%)؛ ومع ذلك، كان أكثر الأمراض المزمنة شيوعًا هو داء السكري(13%). تم تطعيم 82% من المشاركين؛ وكانت أكثر أنواع اللقاحات التي تم إعطاؤها شيوعًا هي لقاح سينوفارم وسبوتنيك (24%). بعد التطعيم، لم يصاب 71% من المشاركين بعدوى كوفيد-19، بينما أصيب 29% منهم بالعدوى. فيما يتعلق بهذه الدراسة، بعد الإصابة بفيروس كورونا المستجد (كوفيد-19)، لم يعاني 66% من المشاركين من أي مضاعفات، ولكن 17% منهم أصيبوا بمضاعفات رئوية، وهي المضاعفات الأكثر شيوعًا بين المشاركين. أما بالنسبة للمضاعفات التي أعقبت التطعيم، لم يعاني 81% من المشاركين من أي مضاعفات، بينما كانت هناك مضاعفات رئوية وعصبية لدى 7-6% من المشاركين. أظهرت نتائج الدراسة أن المضاعفات الأكثر شيوعًا التي لوحظت بين المشاركين بعد الإصابة بفيروس كوفيد-19 والتطعيم كانت المضاعفات الرئوية والعصبية